Clinical analysis of an anchor nail combined with a titanium cable in the treatment of lower patella fractures. Issue 4 (October 2020) - Dong, Zhijun; Liu, Fuyao; Pan, Yuan; Wu, Shengzhong; Luo, Chunshan
Objective: This study was performed to evaluate the clinical effect of an anchor nail and titanium cable for lower patella fractures and identify an effective treatment. Methods: Thirty-five patients with lower patella fractures were treated using anchor nail and titanium cable technology. The anchor was fixed to the main part of the patella; the lower patella was then fixed. A bone tunnel was created, and the titanium cable was fixed. The fracture was allowed to heal without tension. Postoperative radiographs were obtained at regular follow-up evaluations. The Böstman function scores were used to assess postoperative complications. Results: All patients were followed for an average of 15 months. The fracture healing time ranged from 12 to 24 weeks. The postoperative Böstman function scores were as follows: average, 28.6 points; excellent and good scores in 28 and 7 patients, respectively (100% rate of excellent and good scores). At 6 and 12 months postoperatively, the maximum degree of active extension of the affected knee joint was comparable with that of the healthy contralateral joint. Conclusion: The combination of an anchor nail and titanium cable for lower patella fractures is simple and clinically satisfactory, restores knee function well, and is a worthy orthopedic method.